Targeted Disruption of the Transition Protein 2 Gene Affects Sperm Chromatin Structure and Reduces Fertility in Mice - Zhao, Ming (American Society for Microbiology, 2001)
During mammalian spermiogenesis, major restructuring of chromatin takes place. In the mouse, the histones are replaced by the transition proteins, TP1 and TP2, which are in turn replaced by the protamines, P1 and P2. To investigate the role of TP2, we generated mice with a targeted deletion of its gene, Tnp2. Spermatogenesis in Tnp2 null mice was almost normal, with testis weights and epididymal sperm counts being unaffected. The only abnormality in testicular histology was a slight increase of sperm retention in stage IX to XI tubules. Epididymal sperm from Tnp2-null mice showed an increase in abnormal tail, but not head, morphology. The mice were fertile but produced small litters. In step 12 to 16 spermatid nuclei from Tnp2-null mice, there was normal displacement of histones, a compensatory translationally regulated increase in TP1 levels, and elevated levels of precursor and partially processed forms of P2. Electron microscopy revealed abnormal focal condensations of chromatin in step 11 to 13 spermatids and progressive chromatin condensation in later spermatids, but condensation was still incomplete in epididymal sperm. Compared to that of the wild type, the sperm chromatin of these mutants was more accessible to intercalating dyes and more susceptible to acid denaturation, which is believed to indicate DNA strand breaks. We conclude that TP2 is not a critical factor for shaping of the sperm nucleus, histone displacement, initiation of chromatin condensation, binding of protamines to DNA, or fertility but that it is necessary for maintaining the normal processing of P2 and, consequently, the completion of chromatin condensation.